GMAT Prep Plus 2021 - Kaplan (New York Kaplan, 2020)
Updated for the most recent exam changes, Kaplan's GMAT Prep Plus 2021 has the strategies and practice you need for an advantage on test day. This edition includes 6 online practice tests and our proven test-taking strategies, plus more practice questions and updated videos in the online resources. We're so confident that GMAT Prep Plus 2021 will raise your score that we guarantee it: After studying with the book and online resources, you'll score higher on the GMAT or you'll get your money back. The Best Practice 1,200+ practice questions cover all sections of the test and come with detailed explanations. Six full-length online practice tests in the same shorter format as the revised GMAT help you practice using the same interface and adaptivity you'll see on test day. A 200-question online Quiz Bank lets you select problems by topic, customizing your practice. Questions have been reviewed, revised, and updated by Kaplan's expert teachers. Efficient Strategies and Expert Guidance 1-on-1 academic support from Kaplan faculty on our Facebook page: facebook.com/KaplanGMAT Video workshops with top Kaplan faculty help you master our proven methods and strategies for scoring higher. Kaplan's books and practice questions are written by veteran GMAT teachers who know students-and every explanation is written to help you learn. We know the test. The Kaplan team has spent years studying every GMAT-related document available. We invented test prep. Kaplan has been helping students achieve their goals for over 80 years. Find out more at kaptest.com.